A Dual-Polarized Wideband Parabolic Reflector Antenna With High Aperture Efficiency and Low Sidelobe Level for L/S-Band Satellite Communications - Xiao Ding; Xingxing Yang; Botao Feng; Chow-Yen-Desmond Sim; Sulin Wu; Kwok L. Chung (IEEE Access)
A dual-polarized (DP) wideband parabolic reflector antenna with high aperture efficiency and low sidelobe level is proposed for L/S-band vehicular satellite communications. Initially, a pair of cross-arranged dipoles with etching slots and parasitic branches are utilized to achieve wideband characteristic. Subsequently, a top-loaded parasitic beautified substrate, featuring four pairs of rectangular rings arranged around a flower-shaped radiation patch, is employed to prevent the radiation pattern from splitting into two pieces. Finally, by integrating with a parabolic reflector etched with wind-resistance-reduction holes, a parabolic reflector antenna with sidelobe level suppression and stable high aperture efficiency is constructed. Throughout the design process, the principles of wideband operation and low sidelobe levels are analyzed. Measured results exhibit good electrical performance, including a wide bandwidth of 78.57% (1.7-3.9 GHz), a high gain of $21.75± 2.25$ dBi, a peak aperture efficiency of up to 73%, a high isolation level of better than 20 dB, and a low sidelobe level of less than −22 dB. These characteristics make the proposed antenna suitable for wideband and anti-interference vehicular satellite communications.